Handbook of fourier transform Raman and infrared spectra of polymers - Kuptsov, A. H. (Elsevier, 1998)
A collection of infrared and Raman spectra of 500 natural and synthetic polymers of industrial importance is presented in this book. A large variety of compounds are included, starting with linear polyolefins and finishing with complex biopolymers and related compounds. The spectra were registered using Infrared Fourier Transform Spectrometers in the laboratory of the All-Russia Institute of Forensic Sciences. The IR and Raman spectra are presented together on the same sheet. The accompanying data include general and structure formulae, CAS register numbers, and sample preparation conditions. Features of this book: & bull; Continues the long tradition of publishing specific and standard data of new chemical compounds. & bull; For low-molecular weight substances, complementary IR and Raman spectra are featured on the same sample and printed on the same page. This "fingerprint" data allows the substance of the sample to be identified without doubt. & bull; An important feature of this unique collection of data is the increase in the identification precision of unknown substances. & bull; Peak tables are available in digital (ASCII) format, on a diskette delivered with the book. This allows the user to search for unknowns. & bull; All the spectra in the collection are base-line corrected. This book will be of interest to scientists involved in the synthesis of new polymeric materials, polymer identification, and quality control. Libraries of scientific institutes, research centers, and universities involved in vibrational spectroscopy will also find this collection invaluable.
Includes indexes.
Keywords: Polymers -- Spectra -- Handbooks, manuals, etc.; Fourier transform spectroscopy -- Handbooks, manuals, etc.; Raman spectroscopy -- Handbooks, manuals, etc.; Fourier transform infrared spectroscopy -- Handbooks, manuals, etc.; elektronické knihy; electronic books